Femmes et eau dans le Sertão. Le programme « Un million de citernes » - Daniela Nogueira (Cahiers des Amériques Latines)
This article is the result of a reflection concerning mainstreaming gender in the formulation and implementation of water policies and has as objective to analyze the impact of such policies in women life of Brazilian Semi-Arid region. Problems related to the quality and amount of the water come affecting the most different sectors of society. Front to the complexity of the related challenges of such questions, the necessity of a deep transformation in the adopted approaches so that they contemplate the inherent specificities to the nature of a public policy that has as objective water access democratization. Mainstream gender in the national water management goes in this direction. To serve as a frame for this reflection a water policy that has in its design the gender perspective with the aim to a more democratic development was selected, the «Program One Million Rainwater Harvesting System» (P1MC), whose area includes Brazilian Semi-Arid, traditionally for water lack and its hard conditions of life and poverty. In these regions gender inequality assumes clear traces once the weighed daily load for the water attainment usually falls on women and girls, what implies in a deeper asymmetry in the sexual division of domestic work. Therefore, water issue for these populations is inserted in a wide discussion which articulates power relations; sexual division of labour ; social organization and development.